Penguatan PHBS pada siswa SDN 011 Seludau Kabupaten Tana Tidung - Nimah Hidayatul Laili; Eka Nurul Hidayah Puspa Seruni; Avinda Sari Kanthi Rahayu (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2026)
Clean and Healthy Living Behavior is an essential strategy for improving the health of school-age children and preventing communicable diseases. Limited knowledge of healthy behaviors may negatively affect students' daily hygiene practices at school. This community service program aimed to improve students’ knowledge and awareness of Clean and Healthy Living Behavior at SDN 011 Seludau, Tana Tidung Regency. The program employed health education, interactive discussions, demonstrations, hands-on practice, and evaluation through observation and question-and-answer sessions before and after the activity. The results showed increased student knowledge and awareness regarding healthy living practices. Students were able to demonstrate proper handwashing with soap, identify healthy foods, maintain school cleanliness, and explain disease prevention measures. The program effectively strengthened students’ knowledge and healthy behaviors while supporting the development of a sustainable healthy school environment.